Use of the Copenhagen Burnout Inventory to assess Thai librarians' burnout during the COVID-19 pandemic / Angsurat Raya and Somsak Sriborisutsakul - Raya, Angsurat; Sriborisutsakul, Somsak (Faculty of Information Management, 2022)
This study aims to gather respondents' feedback about the survey instrument developed to assess Thai librarians' burnout level, and to prepare survey administration before launching the main study. 20 Thai librarians from public and special libraries in the government sector were asked to join a rehearsal of using and answering the 46-item questionnaire: 12 items of demographic information, 15 items of working situations during the COVID-19 pandemic, and 19 items of personal, work-related, and client-related burnout measures based on the Copenhagen Burnout Inventory. Findings indicated that majority of the survey questions could be feasible in a full data collection effort.